TRAP1 Improves Diabetic Retinopathy by Preserving Mitochondrial Function - Li Y; Xu W; Zhao G; Guo Y; Wang L; Du Q; Fei Y; Hu X; Hu H; Chen L; Xu Y (Clinical Ophthalmology)
Yuchen Li,1,* Weida Xu,1,* Guiyang Zhao,1,* Yuchen Guo,1 Liyuan Wang,1 Qianming Du,2 Yuxiang Fei,3 Xueteng Hu,1 Haoshen Hu,1 Lixun Chen,1,4 Yidan Xu1,4 1Department of Ophthalmology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China; 2General Clinical Research Center, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China; 3Department of Pharmacy, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China; 4Nanjing Red Cross Eye Bank, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lixun Chen, Department of Ophthalmology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China, Email lixunchen@hotmail.com Yidan Xu, Department of Ophthalmology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China, Email yidanxu7771@gmail.comBackground: Recent studies have demonstrated that mitochondrial dysfunction is pivotal in early diabetic retinopathy (DR). Tumor necrosis factor-associated protein 1 (TRAP1), a mitochondrial chaperone regulating stress responses, remains unexplored in DR pathogenesis.Methods: We established in vivo and in vitro models of DR. Hematoxylin and eosin (H&E) staining was utilized to evaluate retinal lesions in rats. Western blotting, reverse transcription quantitative polymerase chain reaction (RT-qPCR), and immunofluorescence staining were employed to assess TRAP1 expression in the retina. Cell viability, reactive oxygen species (ROS), mitochondrial damage, and TRAP1 expression levels were measured in ARPE-19 cells. RNA sequencing (RNA-seq) identified gene expression and pathway changes in shTRAP1 cells. The role of TRAP1 in ferroptosis in ARPE-19 cells was evaluated with or without ferrostatin-1 (Fer-1) and erastin. Potential ferroptosis-related proteins interacting with TRAP1 were validated using co-immunoprecipitation (CO-IP) techniques. This study confirmed TRAP1’s critical role in the pathogenesis of DR.Results: Our findings elucidate a significant reduction in TRAP1 expression in diabetic rat retinas, particularly in the pigment epithelium. High glucose levels correspondingly diminished TRAP1 expression in ARPE-19 cells, causing decreased cellular viability, increased ROS generation, and mitochondrial dysfunction. Notably, the overexpression of TRAP1 effectively preserved mitochondrial homeostasis under stress, mitigated mitochondrial impairment, and enhanced cellular viability. Importantly, TRAP1 may alleviate hyperglycemia-induced mitochondrial damage by reducing ferroptosis through its interactions with ferroptosis-related proteins, including acyl-CoA synthetase long-chain family member 1 (ACSL1), acyl-CoA synthetase long-chain family member 4 (ACSL4), and cytochrome b5 reductase 1 (CYB5R1).Conclusion: TRAP1 exerts a protective influence on mitochondrial function in ARPE-19 cells. Reduced levels of TRAP1 may play a crucial role as an early contributor to mitochondrial dysfunction in diabetic retinopathy. Furthermore, the association of TRAP1 with ferroptosis improves cellular viability by enhancing mitochondrial resilience against high glucose-induced stressors and preventing cellular ferroptosis.Keywords: diabetic retinopathy, TRAP1, mitochondria, oxidative stress, ferroptosis